A novel sinonasal endoscopy scoring system: the discharge, inflammation, and polyps/edema (DIP) score1. Issue 1 (27th August 2012) - Durr, Megan L.; Pletcher, Steven D.; Goldberg, Andrew N.; Murr, Andrew H.
Abstract Background: There is an increasing need for a validated grading system to assess sinusitis severity as observed on endoscopic examination. Existing endoscopy scales have limitations in complexity, validation, and/or applicability. We present a novel and straightforward endoscopic scoring system measuring discharge, inflammation, and polyps/edema (DIP). The aim of this study is to determine correlation of the DIP score with existing sinus endoscopy scoring systems, and to determine interrater and test‐retest reliability. Methods: This retrospective cohort includes a total of 29 patients who underwent functional endoscopic sinus surgery (FESS) for chronic rhinosinusitis. Sinus endoscopy videos were scored in a random and blinded fashion by 3 rhinologists (S.D.P., A.N.G., A.H.M.) using the Lund‐Kennedy Endoscopic Score (LKES), the Perioperative Sinus Endoscopy (POSE) score, and the DIP score. Pearson correlation coefficients, interrater reliability and test‐retest reliability were determined. Results: The results of this study show that the DIP score correlates well (p < 0.0001) with the existing LKES and POSE (Pearson correlation coefficients of 0.78 and 0.90, respectively). The interrater reliability intraclass correlation coefficient (ICC) is highest for the DIP score (0.87), followed by the POSE score (0.84) and the LKES (0.78). Test‐retest reliability ICC is highest for the DIP score (0.78), followed by the POSE score (0.59) and the LKES (0.53). Conclusion: The DIP score is a novel and straightforward endoscopic sinus scoring system that shows substantial test‐retest and interrater reliability in the post‐FESS population. It also demonstrates a high correlation with existing scoring parameters (LKES and POSE). © 2013 ARS–AAOA, LLC.